(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
Literature data concerning empirical and semiempirical correlation equations and parameters obtained by kinetic, spectroscopic (UV, IR, NMR) and thermodynamic methods, which characterize the solvent and which are being used to discuss different reaction series have been analysed. Correlations between considered parameters have been established. In the present communication the application of multiparametric correlation equations to analyse radical and nonradical reactions has been discussed. It has been shown that parameters characterizing the solvents may be used to examine the action of specific as well as nonspecific solvation’s effect, but also to classify the solvents.